2012
DOI: 10.1080/17470218.2011.619661
|View full text |Cite
|
Sign up to set email alerts
|

Judgement of discrete and continuous quantity in adults: Number counts!

Abstract: Three experiments involving a Stroop-like paradigm were conducted. In Experiment 1, adults received a number comparison task in which large sets of dots, orthogonally varying along a discrete dimension (number of dots) and a continuous dimension (cumulative area), were presented. Incongruent trials were processed more slowly and with less accuracy than congruent trials, suggesting that continuous dimensions such as cumulative area are automatically processed and integrated during a discrete quantity judgement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
104
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(122 citation statements)
references
References 32 publications
13
104
4
1
Order By: Relevance
“…This result converges with previous findings showing that individuals with better arithmetic skills show less interference of incongruent total area in numerosity comparison (Guillaume et ASSESSING THE APPROXIMATE NUMBER SYSTEM al., 2013) and more interference of numerosity in aggregated area comparison (Nys & Content, 2012). It is also in line with the claim from Gilmore and colleagues (2013) that inhibiting irrelevant cues might actually be the correlating factor between performance in discrimination tasks and math ability.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This result converges with previous findings showing that individuals with better arithmetic skills show less interference of incongruent total area in numerosity comparison (Guillaume et ASSESSING THE APPROXIMATE NUMBER SYSTEM al., 2013) and more interference of numerosity in aggregated area comparison (Nys & Content, 2012). It is also in line with the claim from Gilmore and colleagues (2013) that inhibiting irrelevant cues might actually be the correlating factor between performance in discrimination tasks and math ability.…”
Section: Discussionsupporting
confidence: 83%
“…However, the existence of an intrinsic interplay between continuous visual properties and discrete numerical ones does not necessarily imply that participants do not rely at all on numerical information to judge the numerosity of dot arrays. Nys and Content (2012) and Guillaume and colleagues (2013) reported that visual cues indeed affected performance in the numerical comparison task but also, more importantly, that discrete numerical information impacted the continuous judgment in a non-numerical aggregate surface comparison task. Consequently, we cannot totally exclude any numerical processing in numerical judgment tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuhs & McNeil, 2013;Gebuis, Cohen Kadosh, de Haan, & Henik, 2009;Gebuis & Reynvoet, 2011bGilmore et al, 2013;Hurewitz, Gelman & Schnitzer, 2006;Nys & Content, 2012;Verguts & Fias, 2004;Zorzi & Butterworth, 1999).…”
Section: Inter-relations Among the Indicesunclassified